1947
DOI: 10.1021/ie50447a637
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Derivatives of Ethane

Abstract: Production of CC12F2, Ib./cu. ft. 50 70 90 reactor/hr. 15 44 440tion, the rate of production over a longer period would be somewhat lower, depending upon the fraction of the total time spent in regeneration.The recycling of triehlorofluoromethane has been shown to be feasible in process III. This variation of the process requires essentially no change in conditions, causes no appreciable change in yield or utilization of hydrogen fluoride, and causes a slight increase in the rate of production of dichlorodiflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As a result, a mixture of mono-, di-, and trichloride (CF 3 CH 2 Cl, CF 3 CHCl 2 , CF 3 CCl 3 ) was formed (Scheme 6). 34 Similarly, radical chlorination of 1,1-difluoroethane gave a mixture of monochloride CF 2 ClCH 3 and dichloride CF 2 ClCH 2 Cl in 70% and 6% yield, respectively. It should be noted that CF 2 HCH 2 Cl is not formed under these conditions.…”
Section: Halogenation Of Ethylenes and Ethanesmentioning
confidence: 98%
See 2 more Smart Citations
“…As a result, a mixture of mono-, di-, and trichloride (CF 3 CH 2 Cl, CF 3 CHCl 2 , CF 3 CCl 3 ) was formed (Scheme 6). 34 Similarly, radical chlorination of 1,1-difluoroethane gave a mixture of monochloride CF 2 ClCH 3 and dichloride CF 2 ClCH 2 Cl in 70% and 6% yield, respectively. It should be noted that CF 2 HCH 2 Cl is not formed under these conditions.…”
Section: Halogenation Of Ethylenes and Ethanesmentioning
confidence: 98%
“…However, while in the case of bromination the selectivity was rather high, it was difficult to control the chlorination of CF 3 CH 3 . As a result, a mixture of mono-, di-, and trichloride (CF 3 CH 2 Cl, CF 3 CHCl 2 , CF 3 CCl 3 ) was formed (Scheme ) …”
Section: Synthesis Of Polyfluorinated Ethanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, R-134a was mentioned as a possible refrigerant in a 1959 patent, 38 and it was mentioned in the chemical literature in 1936. 39 The first investigation of R-123 was as an anesthetic in 1946 by Robbins, 40 who used material prepared by McBee et al 41 2.4.1. National Bureau of Standards (NBS) Study of Alternatives.…”
Section: Evolving Constraints and Refrigerant "Generations"mentioning
confidence: 99%
“…Although the thermal bromination and chlorination of 1,1,1-trifluoroethane have been reported (5)(6)(7), only the chlorination of 1,1-difluoroethane has been reported (7,3). It was found that if ethylidene fluoride was thermally chlorinated with an excess of chlorine, competing reactions took place.…”
mentioning
confidence: 99%